Therapeutic hypothermia as a treatment option after out-of hospital cardiac arrest: our experience - Amer Iglica; Amina Godinjak; Edin Begić; Enisa Hodžić; Faris Zvizdić; Nihad Kukavica; Kenana Aganović; Nirvana Šabanović-Bajramović; Adis Kukuljac; Refet Gojak (Medicinski glasnik, 2019)
Aim: To examine the effects of therapeutic hypothermia on the outcome of patients with the diagnosis of out-of-hospital cardiac arrest (OHCA). Methods: The study included 76 patients who were hospitalised at the Medical Intensive Care Unit (MICU) of the Clinical Centre University of Sarajevo, with the diagnosis of out-of-hospital cardiac arrest, following the return of spontaneous circulation. Therapeutic hypothermia was performed with an average temperature of 33 o C (32.3-34.1 o C) on the patients who had coma, according to the Glasgow Coma Scale (GCS). Results: Multiple organ dysfunction syndrome (MODS) significantly affected survival (p=0.0001), as its presence reduced patients' survival by 96%. In addition, ventricular fibrillation (VF) as the presenting rhythm, also significantly affected survival (p=0.019). A degree of patient's coma, as measured by the GCS, significantly affected survival (p=0.011). For each increasing point on the GCS, the chance for survival increased twice. Moreover, other physiological factors such as the pH and the lactate serum levels significantly affected patients' survival (p=0.012 and p=0.01, respectively). Conclusion: In patients with the diagnosis of OHCA who underwent to the treatment with therapeutic hypothermia, verified VF as a presenting rhythm was a positive predictive factor for their outcome. Therefore, therapeutic hypothermia represents an option of therapeutic modality for this type of patients.
Keywords: intensive care unit; treatment; ventricular fibrillation